Improving Student Learning Outcomes through the Take and Give Cooperative Learning Model Based Audio-Visual Media - Yusdi Mahendra; Rohana Rohana; Faidah Yusuf (ETEDU : Elementary of Teacher Education, 2025)
The problem in this study is the low learning outcomes of science. The purpose of the study is to describe the application of the Take and Give type Cooperative learning model assisted by audio visual media to improve student learning outcomes in the science subject Class V of SD Negeri Batulaccu, Panakukang District, Makassar City, the approach used is qualitative descriptive and the type of research is Classroom Action (PTK). The data collection techniques used are observation, tests and documentation. The results of the study showed that in the achievement of the first cycle of the first meeting, the activities of teachers and students were in the category of lacking, while in the second meeting the activities of teachers and students were in the category of adequate, and the learning outcomes of students in the first cycle were as many as 12 students who completed with a percentage (63.15%) and in the category of incomplete as many as 7 students with a percentage (36.84%). In the achievement of the second cycle, the activities of teachers and students were in the good category, while in the second meeting, the activities of teachers and students were also in the good category, and the learning outcomes of students in the second cycle were16 students complete with a percentage (84.21%) and in the incomplete category with a percentage (15.78%). The conclusion of this study is the application of the Take and Give type cooperative learning can improve participant learning outcomes education.